THE DESIGN AND BUILD AN AUTOMATIC ASSESSMENT RESULT MONITORING SYSTEM ON SHOOTING LESSONS TO SUPPORT TRAINING RAPID MOVEMENT FORCE COMMAND - Suprayitno, Suprayitno; Husein, Sandra (JOURNAL ASRO, 2024)
The Rapid Action Force Command (Kopasgat) carried out shooting exercises regularly with high intensity. However, the current assessment system is still conventional, requires large human resources and tends to be prone to errors and fraud. This research aims to design and build a monitoring system for automatic assessment results on shooting ranges to support Kopasgat exercises. This system was developed using Java technology for application development, MySQL as a database for storing information on assessment results, and an executive information system for effective data presentation. The communication method between devices and systems is implemented through serial communication, ensuring fast and accurate data transmission. The advantage of this system lies in its real-time capabilities, allowing for direct monitoring of the results of the fire assessment instantly. The development process includes analyzing user needs, designing system architecture, developing applications using the Java programming language, and implementing MySQL databases. The system provides comprehensive information, including detailed assessment of shot accuracy, response time, and individual performance of personnel. With this automatic monitoring system, it is hoped that Kopasgat shooting training can be optimized, increasing the efficiency, accuracy, and effectiveness of personnel performance evaluation. The implementation of real-time technology is a key aspect in providing quick feedback to personnel, allowing for immediate improvements and improved overall fireability. Keywords: Communication Series, Executive Information System, Java, Monitoring System, MySQL, Real-time.